Community-Based Control of Aedes aegypti By Using Mesocyclops in Southern Vietnam - Nam, Vu Sinh (The American Society of Tropical Medicine and Hygiene, 2012)
We previously reported a new community-based mosquito control strategy that resulted in elimination of Aedes aegypti (Linn.) in 40 of 46 communes in northern and central Vietnam, and with annual recurrent total costs (direct and indirect) of only $0.28–$0.89 international dollars per person. This control strategy was extended to four provinces in southern Vietnam in Long An and Hau Giang (2004–2007) and to Long An, Ben Tre, and Vinh Long (2005–2010). In a total of 14 communes with 124,743 residents, the mean ± SD of adult female Ae. aegypti was reduced from 0.93 ± 0.62 to 0.06 ± 0.09, and the reduction of immature Ae. aegypti averaged 98.8%. By the final survey, no adults could be collected in 6 of 14 communes, and one commune, Binh Thanh, also had no immature forms. Although the community-based programs also involved community education and clean-up campaigns, the prevalence of Mesocyclops in large water storage containers > 50 liters increased from 12.77 ± 8.39 to 75.69 ± 9.17% over periods of 15–45 months. At the conclusion of the study, no confirmed dengue cases were detected in four of the five communes for which diagnostic serologic analysis was performed. The rate of progress was faster in communes that were added in stages to the program but the reason for this finding was unclear. At the completion of the formal project, sustainability funds were set up to provide each commune with the financial means to ensure that community-based dengue control activities continued.